A low level of CD16 pos monocytes in SARS-CoV-2 infected patients is a marker of severity - Vasse, Marc; Zuber, Benjamin; Goubeau, Laurie; Ballester, Marie-Christine; Roumier, Mathilde; Delcominette, Frédérique; Habarou, Florence; Jolly, Emilie; Ackermann, Felix; Cerf, Charles; Farfour, Eric; Pascreau, Tiffany (Clinical chemistry and laboratory medicine, 2021)
Severe forms of coronavirus disease 2019 (COVID-19) are characterized by an excessive production of inflammatory cytokines. Activated monocytes secrete high levels of cytokines. Human monocytes are divided into three major populations: conventional (CD14 CD16 ), non-classical (CD14 CD16 ), and intermediate (CD14 CD16 ) monocytes. The aim of this study was to analyze whether the distribution of conventional (CD16 ) and CD16 monocytes is different in patients with COVID-19 and whether the variations could be predictive of the outcome of the disease. We performed a prospective study on 390 consecutive patients referred to the Emergency Unit, with a proven diagnosis of SARS-CoV 2 infection by RT-PCR. Using the CytoDiff™ reagent, an automated routine leukocyte differential, we quantified CD16 and CD16 monocytes. In the entire population, median CD16 and CD16 monocyte levels (0.398 and 0.054 × 10 /L, respectively) were in the normal range [(0.3-0.7 × 10 /L) and (0.015-0.065 × 10 /L), respectively], but the 35 patients in the intensive care unit (ICU) had a significantly (p<0.001) lower CD16 monocyte count (0.018 × 10 /L) in comparison to the 70 patients who were discharged (0.064 × 10 /L) or were hospitalized in conventional units (0.058 × 10 /L). By ROC curve analysis, the ratio [absolute neutrophil count/CD16 monocyte count] was highly discriminant to identify patients requiring ICU hospitalization: with a cut-off 193.1, the sensitivity and the specificity were 74.3 and 81.8%, respectively (area under the curve=0.817). Quantification of CD16 monocytes and the ratio [absolute neutrophil count/CD16 monocyte count] could constitute a marker of the severity of disease in COVID-19 patients.